IJCM_346A: The Impact of Depression and Its Associated Factors in Sleep Among General Population in Perambalur- A Cross-Sectional Study - Aswin A; Sivashakthimani (Wolters Kluwer Medknow Publications, 2024)
Background: Sleep which is directly related to health and quality of life is a basic need for human beings to continue their bio-psycho-social and cultural functions. Sleep deprivation appears to have both global and specific effects on cognition, presumably due to the differential susceptibility of various functionally interdependent brain systems to sleep loss. Sleep deprivation can deteriorate general health and is known to be the reason for the development of several co-morbidities such as diabetes and obesity, and hypertension. Objective: To assess the quality of sleep among the general population in Perambalur and investigate the relationship between depression and sleep quality. Methodology: A Cross-Sectional study was conducted between December 2022 to February 2023 in Perambalur municipality for the General public. A pre-tested semi-structured proforma was used to collect data. The objective was assessed using a questionnaire made up with the help of the Pittsburg Sleep Quality Index (to assess sleep), and Patient Health Questionnaire 9 (to assess depression). Data were collected and analysed after obtaining informed consent. Data analyses were done by using the chi-square test. For the comparison of sleep and depression multivariable logistic regression is used. Results: In this study with 650 participants 41.4% are male and around 73.8% had higher education. Those with minimal depression are 59.2% and those having good sleep are 78.2%. The participants who had organised work had no depression (67.1%) which is statistically significant Conclusion: The conclusion showed that quality of sleep in general population was poor and had their depression levels were elevated. Depression was more prevalent among females. Researchers, government and corporate sectors are encouraged to assess the public well being, working hours, metal status of the people with awareness programs, camps and workshops.